Analisis Karakter Mandiri Dalam Kegiatan Outdoor Siswa Kelas III Sekolah Dasar - Ninis Ayu Suryani; Badruli Martati; Fajar Setiawan (Departement of Mathematics Education, 2023)
Basically, character education is a conscious and planned effort to educate and empower students' potential in building their personal character so that they can become individuals who benefit themselves and their environment. Independent is doing activities that are done alone without help and without depending on others. In order for class III students to have independent character, outdoor activities are needed. Outdoor activities are learning that is carried out outside the classroom which is fun because you can enjoy the outdoors created by God Almighty. The purpose of this study was to analyze the independent character of class III outdoor activities at SD Muhammadiyah 16 Surabaya. The method used is descriptive qualitative. Data collection techniques using observation, documentation and interview techniques. The research subjects were third grade students at SD Muhammadiyah 16 Surabaya. Based on the results of this study, it can be concluded that students are able to practice outdoor activities in their daily activities independently. Students are no longer dependent on other people such as parents, teachers and friends. Outdoor activities make students more enthusiastic about learning and make students think more critically.